UTILIZATION OF IJUK’S FIBER AS MATERIAL OF PARTICLE’S BOARD - Annisa Nurul Hidayah; Ayu Mustika Sari (Jurnal PPI Dunia, 2018)
The particle board is an artificial board that uses a mixture of organic adhesives.This board is one ofalternative ways because use ijuk’s fiber as the material which mixed with plastic waste matrix of glassmineral water. The purpose of this experiment was to compare the particle physics of the particle board,on parameter comparison (Jappanese Standard Associaton (JIS) A 5908-2003 and Indonesian NationalStandard (SNI) 03-2105-1996.The method used consisted of the process of preparation of tools andmaterials, weighing matrix and ijuk’s fiber, particle printing using hotpress machine, cooling andtesting of board characteristics include density, water absorption and thickness development Based onexperimental particle board materials obtained density ranges from 0.50 - 0.90 gram / cm3, waterabsorption 16.38% - 18.63% for 1: 4 and 7.76% - 13.99% for 1: 5 material comparison and thicknessdevelopment 0.00% - 8.20% for material comparison 1: 4 and 0.56% - 2.60% for 1: 5 materialcomparison.